A new combination strategy to enhance apoptosis in cancer cells by using nanoparticles as biocompatible drug delivery carriers - Kucuksayan, Ertan; Bozkurt, Fatih; Yilmaz, Mustafa Tahsin; Sircan-Kucuksayan, Aslinur; Hanikoglu, Aysegul; Ozben, Tomris (NATURE PORTFOLIO, 2021)
Some experimental and clinical studies have been conducted for the usage of chemotherapeutic drugs encapsulated into nanoparticles (NPs). However, no study has been conducted so far on the co-encapsulation of doxorubicin (Dox) and epoxomicin (Epo) into NPs as biocompatible drug delivery carriers. Therefore, we investigated if co-encapsulation of doxorubicin (Dox) and/or epoxomicin (Epo) into NPs enhance their anticancer efficiency and prevent drug resistance and toxicity to normal cells. We synthesized Dox and/or Epo loaded poly (lactic-co-glycolic acid) (PLGA) NPs using a multiple emulsion solvent evaporation technique and characterized them in terms of their particle size and stability, surface, molecular, thermal, encapsulation efficiency and in vitro release properties. We studied the effects of drug encapsulated NPs on cellular accumulation, intracellular drug levels, oxidative stress status, cellular viability, drug resistance, 20S proteasome activity, cytosolic Nuclear Factor Kappa B (NF-kappa B-p65), and apoptosis in breast cancer and normal cells. Our results proved that the nanoparticles we synthesized were thermally stable possessing higher encapsulation efficiency and particle stability. Thermal, morphological and molecular analyses demonstrated the presence of Dox and/or Epo within NPs, indicating that they were successfully loaded. Cell line assays proved that Dox and Epo loaded NPs were less cytotoxic to single-layer normal HUVECs than free Dox and Epo, suggesting that the NPs would be biocompatible drug delivery carriers. The apoptotic index of free Dox and Epo increased 50% through their encapsulation into NPs, proving combination strategy to enhance apoptosis in breast cancer cells. Our results demonstrated that the co-encapsulation of Dox and Epo within NPs would be a promising treatment strategy to overcome multidrug resistance and toxicity to normal tissues that can be studied in further in vivo and clinical studies in breast cancer.
Keywords: NF-KAPPA-B; PROTEASOME INHIBITORS; CO-DELIVERY; MULTIDRUG-RESISTANCE; MEDIATED APOPTOSIS; DOXORUBICIN; EXPRESSION; PATHWAY; CYTOTOXICITY; CARFILZOMIB; Science & Technology - Other Topics